Pemaknaan Time Driven Activity Based Costing Produk Perbankan Syariah: Sebuah Fenomenologi Tauhid - Bulutoding, Lince; binti Saban, Azizah; Supriadi; Syariati, Namla Elfa; Sombolayuk, Wilhalminus; Muchlish, Mustakim; Sari, Nur Rahma (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
The purpose of this study is to reveal and interpret the calculation of the cost of determining wadiah yad dhamanah savings at Bank Syariah Indonesia (BSI) based on activities that use the concept of sharia and spiritual time driven activity-based costing (SSTDABC). Time Driven Activity Based Costing (TDABC) has a weakness in cost calculation because it does not take into account cognitive time distortion (CTD) owned by human resources. This can lead to irrelevant revenue and cost assessments that will affect managers' decision-making. The Interpretive method of monotheistic phenomenology used in this study includes noema, noesis, epoche (bracketing), intentional analysis, and eidetic reduction to reveal the phenomena experienced by participants related to determining activity-based costs so as to produce an Islamic banking product (wadiah yad dhamanah). The results of this study reveal that sharia and spiritual time driven activity-based costing can be developed in Islamic banking. The SSTDABC concept will become the “spirit” for the management of Islamic banks in the world and in Indonesia in particular. SSTDABC can be a new input for the development of theory both in the field of service companies and in the field of industry globally and nationally.